Konsep Teknologi Pendidikan Pada Penerapan Pembelajaran Agama Islam - Syaefrudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Theconcept of Islamic religious education is sourced from the Al-Qur'an and Hadith, it has a very important role, it is also a determinant in shaping human characteristics, PAI does not only discuss worship but there is also the issue of muamalah, therefore it is the responsibility of religious teachers/PAI teachers it is very hard, it is not easy, PAI teachers must prepare the material to be delivered to their students so that they can be skilled both vertically and horizontally. The right strategic step in recent times is to take advantage of the technology that is around us, because technological tools are very helpful in facilitating the teaching and learning process in elementary, secondary and even tertiary educational institutions, especially Islamic-based educational institutions that contain Islamic religious subjects, in the process of implementing Islamic learning, good technology is needed so that it can support a better and more effective learning process.